The Swarming Bacillus species in Fishery Products - Thampuran, Nirmala; P.K., Surendran (Fishery Technology, 2025)
The swarming Bacillus species that are encountered in fishery products were found to be B. subtilis, B. coagulans, B. alvei, B. pumilus, B. brevis and B. megatarium. Variation in colony size among individual specieswas quite evidentwhich could be attributed to strain variation.